Polyphonic parenting debate in Russian social media: A pragmatic perspective - Claudia Zbenovich (Russian Journal of Linguistics)
The article examines the evolution of a new language for discussing private and personal matters in the public space of Russian social media. The goal of the study is to reveal the formats of talk that may serve the manifestation of the new public language, reflected in multiple discourses through which Russian parents position themselves in the Internet parenting forum debate. The data for the research were obtained from the conversation analysis of parents’ posts on Alpha Parenting, a popular Russian Facebook community platform. The study aimed to analyze more than 400 posts of parents of young children (6-12 years old) uploaded from 2017 to 2019. The emerging formats of talk are examined from a perspective of pragmatic communicative acts that shape the interactional situation in a chat forum. An interplay of the multiple forms of talk in the online forum is understand through the prism of Bakhtin’s analytical apparatus, which is based on the concepts of voice and polyphony . The results illustrate the simultaneous presence of different languages in public discussions of private life. These may pertain either to everyday informal communication constituted in the private and interpersonal sphere, to discursive practices of authoritative talk, to the meta-ways of discourse monitoring and management, or no less important, to the therapeutic public emotional talk about one’s private inner world and emotional experience. The study suggests that the ways of communicating about emotions represent an emerging emotional therapeutic attitude and language that has been regulating and reshaping Russian Internet communication.